Techno-Economic feasibility of pen aquaculture for enhancing fish yield from Floodplain Lake of Manipur, India - Debnath, D.; Yengopam, S.; Bhattacharjya, B. K.; Yadav, A. K.; Das, P.; Sarma, K. K.; Das, B. K. (Journal of the Inland Fisheries Society of India, 2022)
Pen aquaculture is a technology suitable for growing fish in enclosures erected in large open waterbodies such as floodplain wetlands and reservoirs. In the present study, techno-economic feasibility of pen aquaculture for growing table-fish in a floodplain lake of Manipur, India was assessed. Four pens were constructed using nylon net (35 mm mesh size) supported by bamboo poles each measuring 0.25 ha area at Takmu pat, Bishnupur District, Manipur. The pens were stocked with advanced fish fingerlings (87.00- 151.79 g) at a stocking density of 8,200 fingerlings ha-1 after manual clearance of aquatic macrophytes and removal of unwanted aquatic organisms through repeated netting. Seven species of carps including Indian major carps (Catla, Labeo catla; rohu, L. rohita and Mrigal, Cirrhinus mrigala), exotic carps (Grass carp, Ctenopharyngodon idella; Silver carp, Hypophthalmichthys molitrix and common carp, Cyprinus carpio) and minor carp (Kuri, L. gonius) were stocked. Each pen was stocked with Catla (100 nos.), Rohu (500), Mrigal (500), Common carp (250), Grass carp (250), Silver carp (200) and Kuri (250 nos.). Fishes were fed with commercially available pelleted feed at 2-3% of body weight twice-a-day. After rearing for 12 months, catla was observed to have significantly higher growth performance in terms of weight gain% and specific growth rate, followed by grass carp. Rohu, Mrigal and common carp had similar growth performance while RESEARCH PAPER silver carp had the least growth. Survival of the fish ranged from 60.75 to 92.80%. A net fish production of 6124 kg ha-1yr-1 from the pens and benefit-cost ratio of 1.53 suggested pen aquaculture in net enclosures was a techno-economically feasible strategy, having high potential to enhance fish yield from the pats/ floodplain lakes of Manipur. Key words Pen culture; Takmu pat; Major carp; Minor carp; Exotic carp; Fish growth